Новые для фауны УССР виды гамазид рода Amblyseius Веrlеsе, 1904 (Parasitiformes, Phytoseiidae) - Вайнштейн, Б.А.; Щербак, Г.И. (Вестник зоологии, 1972)
A description and drawings are presented of mites Amblyseius meridionalis (B e r l e s.e, 1914), A. obtusus (Koch, 1839), A. neobernhardi Athias-Henriot, 1966, A. agtestis Zarg, 1960, .A. marginatus Wainstein, 1961, A. umbraticus (Chant, 1950), A. aurescens Athias-Henriot, 1961, A. barkeri (Hughes, 1948), A. ovi¬cinctus Athias-Henriot, 1961.